Feasibility Study of the Pagar Sayuran Organik Business - Garjito, Redi; Herdinata, Christian (KnE Social Sciences, 2021)
Modern cultivation supports better lifestyles in urban society where initially people think that it is only possible to conduct cultivation activities in remote or large areas, which restricts urban people to create friendly urban cultivations. Therefore, Pagar Sayuran Organik established a modern design of equipment for hydroponic cultivation. This research aimed to discover the feasibility of business development from the existing business, covering 5 research aspects: Market and Marketing, Technical and Technology, Legal, Financial and Human Resources. The population in this study was people of Gresik Regency that had significant population growth and housing developments, so that they were expected to become potential consumers. This study discovered that Pagar Sayuran Organik has fulfilled the 5 aspects’ requirements Therefore, the Pagar Sayuran Organik business is feasible to develop. Keywords: Hydroponics Starterkit, organic vegetables, hydroponics, feasibility study